The Making of the Humanities : volume II From Early Modern to Modern Disciplines Volume II - From Early Modern to Modern Disciplines - Maat, Jaap (Amsterdam University Press, 2012)
This much-awaited second volume investigates the changes in subject, method and institutional context of the humanistic disciplines around 1800, offering a wealth of insights for specialists and students alike. Point of departure is the pivotal question whether there was a paradigm shift in the humanities around 1800 or whether these changes were part of a much longer process. The authors provide an overarching perspective including philology, musicology, art history, linguistics, historiography, philosophy and literary theory. They also make clear that the influence from the East, from the Ottoman Empire to China, was crucial for the development of the European humanistic disciplines.